Re-writing the Official Narrative of Bloody Sunday: The Role of Photographs - Charlotte Barcat (Revue LISA)
On 15 June 2010, the Bloody Sunday Inquiry, also known as the Saville Inquiry, published its report about the events of 30 January 1972. Thirty-eight years had passed since the first public inquiry led by Lord Widgery had published its report, which many at the time had dubbed the “Widgery Whitewash.” This article proposes to examine the role of photographs in the re-writing of the official version of Bloody Sunday, both in the deconstruction of the Widgery report and in the reconstruction of the new official version by Lord Saville. Indeed, while the version of events set out in the Widgery report remained the official one, photographs could be a powerful means of subversion: their emotional power could be very efficient to shock the public into awareness. They were thus used in several of the books that helped make the case for the new inquiry. After the setting up of the Saville Inquiry, they also proved very helpful by helping to reconstruct the sequence of events minute by minute. Arguably, the Saville Inquiry, by re-integrating them into the official version, also gave official recognition to these “fragments of truth” that had been mostly disregarded by Widgery.